AUTHENTIC ASSESSMENT BASED ON TEACHING AND LEARNING TRAJECTORY WITH STUDENT ACTIVITY SHEET (SAS) ON BASIC PHYSICS COURSES - Chaerul Rochman; Ea Cahya Septian Mahen; Dindin Nasrudin (Universitas Pendidikan Indonesia (UPI), 2018)
AbstrakTujuan penelitian ini untuk mendapatkan profil capaian pembelajaran dengan mennggunakan model Authentic Assessment Based on Teaching Learning Trajectory (AABTLT) with Student Activity Sheet (SAS) pada mata kuliah Fisika Dasar 1. Metode yang digunakan weak experiment dengan the one shoot case study design, yaitu ada dua kelompok mahasiswa yang diberi perlakuan presentasi-diskusi AABTLT with SAS pada materi gerak satu dimensi. Sampel penelitian adalah 70 orang mahasiswa yang mengikuti kuliah Fisika Dasar Instrumen penelitian yang digunakan adalah SAS yaitu daftar jawaban mahasiswa terhadap pertanyaan, instruksi dan tagihan selama proses perkuliahan. Data yang diperoleh dari SAS akan dianalisis secara kuantitatif sederhana dan diinterpretasikan dengan teknik kualitatif. Penelitian ini menyimpukan bahwa (1) perkuliahan dengan presentasi dan penyajian model AABTLT dengan SAS dapat menggambarkan keefektifan, (2) terdapat perbedaan tingkat efektifitas capaian pembelajaran antara kedua kelompok mahasiswa kurang dari 10%. Kata Kunci: Authentic Assessment Based on Teaching Learning Trajectory (AABTLT); Fisika Dasara; Student Activity Sheet (SAS) AbstractThe purpose of this research is to get the learning achievement profile by using the Authentic Assessment Based on Teaching Learning Trajectory (AABTLT) model with the Student Activity Sheet (SAS) in 1st Basic Physics Course. The method used by the weak experiment with the one shoot case study design, there were two groups of students who were treated with AABTLT-SAS presentations on one-dimensional motion material. The sample of research is 70 students who attended 1st Basic Physics. The research instrument used is SAS which is the list of student answers to questions, instructions, and bills during the lecture. Data obtained from SAS will be analyzed in a simple quantitative manner and interpreted with qualitative techniques. This study concludes that (1) lectures with presentation and presentation of AABTLT model with SAS can describe the effectiveness of Basic Physics, (2) there is the difference of effectiveness level of learning achievement between both groups of students less than 10%. Keywords: Authentic Assessment Based on Teaching Learning Trajectory (AABTLT); Basic Physics; Student Activity Sheet (SAS)